PENGEMBANGAN APLIKASI DIGITAL LIBRARY MENGGUNAKAN METODE WATERFALL BERBASIS ANDROID - MEMORI MANALU, FRIA ANJU; Fajrin, Alfannisa Annurullah (Computer Science and Industrial Engineering, 2024)
SMPN 40 Batam Library implements a library information system. Currently, because library data information management is still very conventional, errors in checking data and difficulties in finding data information still often occur in library data management. Along with the development of library needs, it is important to realize that the data management process, including member data, book data, data borrowing, data returning, and data library are still done manually. The main objective of implementing a library information system is to facilitate the smooth processing of data and information in the library, especially for library staff. This aims to ensure that book borrowers can more easily access various information related to the book collections available in the library. For digital library development, the first is small-scale development. The digital library application was created using Adobe Animate software and Adobe AIR as the programming language. The data collection method uses the waterfall method which is carried out in stages, namely needs analysis, design, implementation, testing and maintenance. Design stages use Unified Modeling Language (UML) such as use case diagrams, activity diagrams, sequence diagrams, and class diagrams. And system testing adopts black box testing. The research results show that the digital library system has succeeded in building Android-based applications that can be run on mobile devices. Digital library applications are more convenient for administrators to use, managing book data and querying book information and making library reports more efficient.